1) 0.7x=-4.2
x=6
2)-1,4-5,6=7
3)4/5x=1
4=5x
x=0.8
4)9=-6x
x=-1.5
5)3=-48x
x=- 1/16
6)3x=7
x=7/3
7)-2.1/2x=7/15
140x= -315
x=-9/4
a) x∈ (-∞;3)
b) x∈ (-∞;0] ∪ [4;+∞)
c) x∈ (-∞;0)∪(0;2/3)
d) x∈ [-1/2;1) ∪ (1;+∞)
Объяснение:
a) f(x)=√(-x+3);
-x+3≥0; -x≥-3; x≤3.
ОО: x∈(-∞;3).
b) f(x)=√(0,5x²-2x); 0,5x²-2x≥0; x(0,5x-2)≥0;
x≥0;
0,5x-2≥0; x≥2/0,5; x≥4; x∈[4;+∞);
x≤0;
0,5x-2≤0; x≤2/0,5; x≤4; x∈(-∞;0];
OO: x∈(-∞;0] ∪ [4;+∞);
c) f(x)=ln(2/x-3);
2/x-3>0; 2/x>3; x<2/3; x∈(-∞;2/3);
x≠0; x∈(-∞;0)∪(0;+∞)
OO: x∈(-∞;0)∪(0;+∞) ∩ (-∞;2/3) ⇒ x∈(-∞;0)∪(0;2/3)
d) f(x)=√(3/(x-1)+2);
3/(x-1)+2≥0; 3+2(x-1)≥0; x≥-1/2; x∈[-1/2;+∞)
x-1≠0; x≠1; x∈(-∞;1)∪(1;+∞)
OO: x∈[-1/2;+∞) ∩ (-∞;1)∪(1;+∞) ⇒ x∈[-1/2;1)∪(1;+∞)
Парабола: y = ах^2 + bx + c
1)
A: 16a - 4b + c = 0
B: 4a + 2b + c = 0
C: 0a + 0b + c = -3
<=>
c = -3
16a - 4b = 3
4a + 2b = 3 (* 2) и сложим
<=>
c = -3
4a - 2b = 3
24a = 9
<=>
c = -3
a = 3/8
b = 2a - 3/2 = -3/4
=> Уравнение: y = 3/8 x^2 - 3/4 x - 3
2) (Другой
Используем Th Виета
x1 + x2 = -b/a
x1 * x2 = c/a
что означает, что a x^2 + bx + c = 0 ?
это значит, что х - корень
т.к. в Точках A и B y = 0 => корни: 1 и 6
=> 7 = -b/a
6 = c/a
Посмотрим на 3-ю точку
a * 0 + b * 0 + c= -4
=> c = -4
=> 7 = -b / a
6 = -4/a
=> a = -2/3
b = 21/2
=> Уравнение: y = -2/3x^2 + 21/2x - 4